Respon al-qur’an terkait fenomena domestifikasi perempuan - Karomah, Maulidatul Lailatul (Maliki Interdisciplinary Journal, 2024)
The domestication of women is an important issue in society. This is related to the role and nature of women in the domestic world. In the context of a society that adheres to patriarchal norms, women are often placed in the role of housekeepers and maintainers of social relations in the domestic environment. Women’s household roles are often underestimated. The fixed division of roles between men and women in the household means that housework does not receive recognition comparable to men’s work in the public sphere. Many women choose to care for children at home, while many men are responsible for earning a living outside. Although the division of domestic and public tasks is intended to create harmony in the household, certain situations can change it. For example, if social conditions encourage women to work outside the home to help the family financially, or if men cannot work, the division of domestic and public tasks must be readjusted. Housework is not only the responsibility of women, nor is work in the public sphere always the domain of men alone.